PREPARATION FOR SELF-RELIANCE BEFORE ENTERING AGING IN THAI-MALAYSIA BORDER AREA: CASE STUDY IN SAMNAK KHAM COMMUNITIES MOO1, SAMNAK KHAM, SADAO DISTRICT, SONGKHLA PROVINCE - Suhaimeen Dorloh; Firhana Malinee; Abdulkhaliq Arrahimee; Sawat Laipaporn; Jirachaya Jeawkok (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
This research is a mixed method. The main purpose of this study to explore the preparation for self-reliance before entering elderly stage among Ban Samnak Kham Moo 1 Communities at Samnak Kham, Sadao, Songkhla. The population sample group for quantitating aged between 20-59-year-olds are 266 samples were collected. Besides that, 12 respondents are being an in-depth interview. Data were analysed using descriptive statistics and content analysis. The results revealed that the overall image level of preparation for into the elderly was moderate (=3.23) the sample was prepared at a high level to include religion and faith (=3.61) Economic (=3.36) and housing (=3.27) respectively. The research findings content 7 major themes for the purpose of understanding the methods to prepare for the elderly which include (1) Economic, there is a need to saving some money for future use and finding an interesting career in becoming a source of income in the future, (2) Health, It must be continuous exercise and eat five useful foods, (3) Housing, Must be adjusted to suit the age range, (4) Social, There must be a strong incentive to participate in social activities. (5) Religion and Faith, apply religion to daily life to be conscious and makes a calm mind. (6) Education should have studied both ordinary knowledge and religious knowledge to be used as the anchor of the soul. (7) Family, family members need to be prepared to cope with the elderly and the family needs to plan for the elderly.